EXPLORING GLOBAL ENGLISHES IN INDONESIAN EFL CLASSROOMS: A CASE STUDY OF EXTENSIVE LISTENING - Maharani, Nabilla; Siti Rodliyah, Rojab; Handi Gunawan, Muhammad (University of Kuningan, 2025)
This study explores how Global Englishes (GE)-informed materials can be used for teaching extensive listening, focusing on students’ perceptions before and after learning the concept, as well as the benefits and challenges they experienced. The study was conducted with 24 third-year university students in Bandung, Indonesia. In this study, data were collected through course reflective journals, semi-structured interviews, and classroom observations and were thematically analysed. The findings revealed that most students were initially not familiar with Global Englishes. However, after learning the concept, they gained a better understanding and awareness of the diversity of English. They also became more confident speaking English with their own accents. A significant challenge, however, was understanding accents they had not been exposed to before. In essence, the findings may elucidate how GE-informed materials can boost students’ confidence and expand their understanding of effective communication in English, as well as provide suggestions for incorporating GELT into classrooms.